Creativity and product innovation as determinants of birdcage business success in Dawuhan Mangli village, Sukowono district, Jember - Wasil Hidayatullah; Adil Siswanto (YAYASAN MITRA PERSADA NUSANTARA, 2026)
The birdcage business is a very promising venture, especially in Dawuhan Mangli Village, Sukowono District. Research shows that the birdcage business has shown strong prospects over the years. 1) How creative are the bird cage entrepreneurs in Dawuhan Mangli Village? 2) How innovative are the products of the bird cage entrepreneurs in Dawuhan Mangli Village? 3). How big is the influence of creativity and product innovation on the success of the bird cage business in Dawuhan Mangli Village? 1) To find out the creativity of bird cage entrepreneurs in Dawuhan Mangli village. 2) To find out the product innovation carried out by bird cage entrepreneurs in Dawuhan Mangli village. 3) To find out how much influence creativity and product innovation have on the success of bird cage businesses in Dawuhan Mangli village. This study concluded: 1) The creativity variable does not have a significant positive effect on the business success variable for Bird Cage Entrepreneurs in Dawuhan Mangli Village. 2) The product innovation variable has a significant positive effect on the business success variable for Bird Cage Entrepreneurs in Dawuhan Mangli Village. 3) The creativity and product innovation variables together have a significant positive effect on the business success variable for Bird Cage Entrepreneurs in Dawuhan Mangli Village.